Perancangan Rencana Strategis Sistem Informasi Pada PT XYZ - Leni Kusneti; Bima Aprianto S; Stenilaus A; Andri Wijaya (CV. ITTC INDONESIA, 2024)
This study develops a strategic plan for Information Systems/Information Technology (IS/IT) at PT XYZ, a distribution company in the plastic packaging sector. The primary objective of the research is to enhance operational efficiency and expand market reach through the optimal utilization of information technology. The methodology employed includes SWOT analysis, PESTLE, and the McFarlan Grid to evaluate the company's internal and external conditions and define the IS/IT implementation strategy. The findings highlight the need for additional features in the Enterprise Business System (EBS) to record retail transactions, the implementation of an e-commerce platform to broaden market access, and the adoption of automation technology in logistics processes to boost productivity. Moreover, the study recommends developing a Customer Relationship Management (CRM) system to strengthen relationships with business partners. A systematically designed five-year implementation roadmap ensures that this strategy supports the company's digital transformation and enhances its performance in the global market.